ANALISIS LAYANAN BIMBINGAN DAN KONSELING DALAM PENANGANAN KESULITAN BELAJAR DI SD INPRES 3 KALABAHI TIMUR - Ariyance Maleipada; Martharia Sengaji, Gamelia Langkamang, Ariel Malaiboti, Yessi Mata, Petrus Mau Tellu Dony, Imanuel Y (CV. Adiba Aisha Amira, 2025)
This study aims to examine Guidance and Counseling Services in Addressing Learning Difficulties at SD Inpres 3 Kalabahi Timur, Alor Regency, and the role of homeroom teachers as counselors in helping students overcome learning difficulties at the same school. The research method used is descriptive qualitative, with data collection techniques including interviews and documentation. The results show that the implementation of guidance and counseling services to address students' learning difficulties at SD Inpres 3 Kalabahi Timur includes: guidance and counseling services are carried out by classroom teachers, as there is no dedicated counseling teacher at the school, and the types of services used include: learning guidance services, individual counseling services, and collaboration with parents or guardians. The role of the homeroom teacher is as a counselor in implementing guidance and counseling services to help students overcome their learning difficulties at SD Inpres 3 Kalabahi Timur, Alor Regency.